An epistemic case study: how businesses exploit consumers in self-care - Kok, Wenyi (Nanyang Technological University, 2023)
Practicing self-care has become prominent in today’s society. When one thinks of self-care, it's easy to think of products and a cozy routine. Many of such ideas are from businesses’ involvement. However, such practices often do not rely on scientific and medical evidence. This paper explores businesses’ exploitation of the public’s belief regarding self-care from an epistemological standpoint. With references to specific companies involved in the topic of self-care, and drawing theories from Fricker, Goldman, Carson, Wokutch and Cox, businesses’ interests for profits, along with its strong influence can shape the public’s belief regarding self-care. I argue that in the long run, businesses’ involvement in the topic of self-care will cause negative epistemic effects on the public’s belief. This manifests itself in four ways: businesses’ lack of expertise, false claims made, lack of medical evidence and its usage of unreliable testimonies. Despite the understanding that there are businesses with a positive involvement in self-care, it may be a case of luck for certain individuals who unjustifiably believe so. Additionally, even with sufficient research and evidence, the public may still end up with false beliefs. I conclude that with consideration of all previous sections, businesses should not be a forefront epistemic resource when one practices self-care.